Systematic Mapping of Corporate Social Responsibility Topics for 2015-2021 Based on Bibliometric Analysis (Public Accounting and Sustainability, 2024)
Research aims: This study used bibliometric analysis to produce a comprehensive mapping of corporate social responsibility (CSR) research. This study examined changes in citations, publication trends, author collaboration, trend title, trend author keywords, trend abstract, nations, dominating factors, research development, and future research in corporate social responsibilities papers from the Scopus index with a range of 2015-2021. Design/Methodology/Approach: This research employed bibliometric analysis methods. The research sample used was 1,567 articles with the keyword "Corporate Social Responsibility." The articles used were sourced from Scopus-indexed journals for 2015-2021, with the help of Publish or Perish (PoP). This bibliometric analysis utilized VOSviewer. Research findings: The year with the most citations, according to statistics, was 2016, with 8,549 citations. Regarding publication trends, most of the papers were published in 2020, namely 352. Mohammad Irfan and Bilal Afsan are the authors with the most networks/collaboration, as many as 332. The term 'Corporate Social Responsibility' is the most commonly used keyword in CSR articles. Four countries linked CSR to the research: 1) Pakistan, 2) Malaysia, 3) Italy, and 4) Indonesia. Co-occurrence network visualization explains the network or relationship from one term to another in research in the field of CSR for the 2015-2021 period. While the visual overlay represents keywords indicating the year of publication, the density visualization signifies research on a topic that is still very broad to be studied. Theoretical contribution/Originality: These findings also indicate that it is essential to recognize the approaches and theories behind the development of CSR to determine the gradual nature of the aspects involved within it. Practitioner/Policy implication: This article calls for greater engagement among academics and CSR researchers to more explicitly consider how their research can contribute to the understanding of CSR. Research limitation/Implication: The limitation of this study is that it only used observation years from 2015-2021, preferably for future researchers to be able to add the most recent observation year. In addition, this study has not explored the application of the literature used; thus, the next researchers are preferably to develop this literature review with the help of other applications, such as Bliblioshiny or R.